Leader Effectiveness In Small Bureaucracies - Miles, Robert H.; Petty, M. M. (Academy of Management Journal, 1977)
An investigation of the relationships between leader initiating structure and consideration and several organizational outcomes tested the conditioning effects of organizational size. The results suggest that leader initiating structure is more effective in smaller agencies than in larger agencies, while the effectiveness of leader consideration does not appear to vary with agency size.